Between scylla and charybdis? covid-induced economic pressures threatening the media in Portugal - Novais, Rui Alexandre (2022)
The European Commission Vice-President conveyed a worrying diagnosis of the news media in her 2021 speech at the Media4Europe Summit. According to Vĕra Jourová, the pandemic further exacerbated the economic crisis of the press sector that had started well before (EuropeMediaLab, 2021). Adding to the considerable income losses in recent decades, the plunging of the advertising revenues of the COVID-19 pandemic worsened the already grim financial situation experienced by the generality of the media sector (Olsen et al., 2020) and threatened to become an ‘extinction event’ (Ahmed, 2020) particularly to the printed press. As a result of the extraordinary scenario, some countries, like Portugal, introduced a temporary aid measure to cushion the economic impact of the pandemic and support professional news journalism in the public interest. Such government intervention in the form of financial support raised some doubts about their effectiveness and state dependency of the press in the long run, and it unveiled the prevailing split in terms of the economic orientation philosophy of the press firms in facing the media industry problems (Holtz-Bacha, 2021, p.44; Murschetz, 2020). Against this backdrop, this study aims to reveal how the media managers in the Portugal dealt with the problematic decision to whether accept some of the exceptional aid to cope with COVID-induced economic pressures or struggle to survive without some form of public support.